Analisis Pengembangan Perkebunan Karet (Studi pada Perkebunan Karet Rakyat di Kabupaten Tapanuli Selatan Provinsi Sumatera Utara) - Mukhlis Mukhlis; Edi Batara Mulya Siregar; Sri Fajar Ayu (JURNAL AGRICA, 2018)
Smallholder rubber plantations in South Tapanuli still have the opportunity and huge potential , especially when associated with a society that is still largely rely on rubber plants as an option for propagation . The availability of potential land is still quite wide and supported by government policy in the development of rubber plants also provide great opportunities to the business development of rubber plants in South Tapanuli . Commodity rubber in South Tapanuli a plantation commodities that contributed greatly to the economic development of society . Development of agri commodities rubber growing along with improving commodity prices of rubber inlocal markets , nationally and internationally. Business financially viable smallholder rubber plantations to be developed . Parameter estimation results show that only a partial area of variable parameters rubber previous year ( when different variables ) that significantly influenced the total area . While other parameters rubber real price , price Rid TBS and dummy effect is not real autonomy to the area ! rubber . Coefficient djfferential positive shift indicates that the partial commodity is a commodity rubber plantations do not have a competitive advantage in all areas South Tapanuli . Competitive advantage and rubber commodity acreage only contained in the district of Batang Toni and Angkola West . Keywords : rubber commodity , institutional farmer , farming , KUD